PENGARUH PENYULUHAN TERHADAP TINGKAT PENGETAHUAN TENTANG PENYAKIT DEMAM BERDARAH DENGUE (DBD) PADA SISWA SEKOLAH DASAR NEGERI 56 BANDA ACEH - Isfanda Isfanda; Andri Andri (Jurnal Sains Riset, 2021)
Dengue hemorrhagic fever remains as a serious problem of public health in Indonesian society. The purpose of health research on DHF is to inform the public about the disease. This research aims to determine the effect of education on the level of knowledge about DHF in elementary school students 56 Banda Aceh. This research uses quasi experiment design. The research was conducted at State Elementary School 56 Banda Aceh. The population of the study were all students of class V, amounting to 62 people. Sample determination is determined by total sampling. The extension instrument is a direct education with lecture method. For data analysis before and after education adopted with Paired T-test. In this research show p value = 0,002 which means that there is significant influence. The results showed that knowledge before being given counseling that is knowledge of medium that is equal to 88,7% (54 people). After education there was a significant increase in knowledge of 100% (62 people). It can be seen from the mean of the mean value of knowledge before and after counseling which shows a significant increase of 5.08. Based on the results of the research, it can be concluded that there is a significant influence on improvement knowledge students of elementary School 56 after being given education.Keywords: DHF, education, knowledge